Head Gesture Recognition and Interaction Techniques in Virtual Reality: a Review - Nasuha Zolkefly, Nurul; Ismail, Ismahafezi; Safei, Suhailan; Nor Wan Shamsuddin, Syadiah; Azhar M. Arsad, Mohd (International Journal of Engineering and Technology, 2018)
This paper presents a review of head gesture recognition using specific models by year timeline. The related minor topics of this project also mainly discuss (a) Virtual Reality interaction techniques, (b) Virtual Reality head gesture interaction, and (c) Mobility Impairments using Virtual Reality (VR) System. This study contributes to an exploration of a different body part of the gestural input, which is the head gesture as the main interaction approach in virtual reality (VR). This review also prepares new insights of head gesture from how the model theoretically recognizes the gesture and implemented as input modality and interaction in virtual reality (VR) environment.Â